SAT-477 Melanoma Treated with Pembrolizumab Leading to Thyroiditis and Subsequent Hypothyroidism - Fishel, Heather (J Endocr Soc, 2020)
Background: Pembrolizumab (PD-1) is an immune checkpoint inhibitor used for treating melanoma and has been associated endocrine immune-related adverse events. Case Presentation: 76-year-old Caucasian male presented for evaluation of abnormal thyroid labs. Significant co-morbidities included recurrent melanoma, heart failure, atrial fibrillation, coronary artery disease, type 2 diabetes, hypertension. Patient’s melanoma was being treated with Pembrolizumab. Further history revealed no family/personal history of thyroid disease but a history of mouth cancer treated with radiation over 30 years ago. He denied any recent glucocorticoid or biotin use. Symptoms included worsening fatigue, weight loss, and diarrhea. He was afebrile and vitally stable. Physical exam was unremarkable. Prior to this year, patient had normal thyroid labs. Recent thyroid labs showed TSH of 0.01 uIU/mL (normal 0.34-4.94 uIU/mL), confirmed with repeat labs a week later (TSH: < 0.01, Free T4: 2.23 ng/dL, normal Free T4: 0.7-1.48 ng/dL). There was a high suspicion that these labs were related to Pembrolizumab, but other etiologies were evaluated. Completed thyroid uptake and scan showed no evidence of increased activity (4-hour uptake: 1.6%, 24-hour update: 1.2%). Repeat thyroid labs indicated recovering thyroid function with a TSH: 0.14 uIU/mL, Free T4: 0.49 ng/dL, Free T3: 1.5 pg/mL (normal Free T3 2.3-4.2 pg/mL), TSI: 96% (normal < 140%), TPO Ab: 111 IU/mL (normal TPO Ab < 9 IU/mL). One month later thyroid tests resulted as TSH: 72.81 uIU/mL, Free T4: < 0.40. He was started on levothyroxine, which was titrated over several weeks. Discussion: Pembrolizumab (PD-1) is an IgG4 programmed cell death 1-directed monoclonal antibody, whose mechanism of action is to inhibit cancer cells ability impede T-cell activation. However, because of this mechanism, some T-cells, will remain activated, leading to autoimmune diseases. PD-1 has been associated with thyroid dysfunction, with an incidence rate as high as 14-20%. The clinical presentation varies from isolated thyrotoxicosis to overt hypothyroidism. In our patient, he developed thyrotoxicosis with subsequent development of hypothyroidism. Generally, the timing of thyroid dysfunction after the initiation of PD-1 ranges from 3 to 40 weeks, with the median onset at week 6. Baseline TSH and free T4 should be obtained with rechecking of these labs monthly for the first 6 months. For patients who present with thyrotoxicosis, Grave’s disease should be ruled out, and initial treatment should include beta-blockers. Hypothyroidism should be treated with levothyroxine with titration to normal thyroid function tests. What remains to be determined is the mechanism in which PD-1 causes thyroid dysfunction and if specific patient characteristics, such as thyroid antibodies, can be used to risk stratify the likelihood of a patient developing thyroid dysfunction.